2012
DOI: 10.1038/nature10981
|View full text |Cite
|
Sign up to set email alerts
|

Engineered two-dimensional Ising interactions in a trapped-ion quantum simulator with hundreds of spins

Abstract: The presence of long-range quantum spin correlations underlies a variety of physical phenomena in condensed matter systems, potentially including high-temperature superconductivity [1,2]. However, many properties of exotic strongly correlated spin systems (e.g., spin liquids) have proved difficult to study, in part because calculations involving N-body entanglement become intractable for as few as N ∼ 30 particles [3]. Feynman divined that a quantum simulator -a special-purpose "analog" processor built using q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
1,030
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 881 publications
(1,053 citation statements)
references
References 47 publications
11
1,030
0
3
Order By: Relevance
“…[86,87]. While in the early theory studies [85,[88][89][90] spin interactions decaying with the third power of the distance were considered, it was experimentally demonstrated that management of phonon dispersion allows to achieve powers between 0.1 and 3 in the 2D arrays of traps [91]. Recent state of art represents the work on experimental realization of a quantum integer-spin chain with controllable interactions [92].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[86,87]. While in the early theory studies [85,[88][89][90] spin interactions decaying with the third power of the distance were considered, it was experimentally demonstrated that management of phonon dispersion allows to achieve powers between 0.1 and 3 in the 2D arrays of traps [91]. Recent state of art represents the work on experimental realization of a quantum integer-spin chain with controllable interactions [92].…”
Section: Discussionmentioning
confidence: 99%
“…The violation is normalized to the corresponding classical bound βc. The blue curve corresponds to (90) and the red curve corresponds to (91). The maximal quantum violation has been plotted in logarithmic scale (in dB) in order to better compare the two bounds; i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies on trapped ion systems focused so far on the simulation of the Dirac equation encoded in motional and internal degrees of freedom of a trapped ion in 3+1 and 1+1 space-time dimensions, and its consequences, such as Zitterbewegung [69] and the Klein paradox [70]. There is, however, a large ongoing effort toward scalable ion systems, employing for instance arrays of microtraps or self-assembled lattices, where several hundreds of ions in a triangular lattice can be stored [71].…”
Section: Confining Atoms and Ionsmentioning
confidence: 99%
“…Cold atom experiments on the triangular lattice, transverse field Ising model are ongoing 13 . Our results provide quantitative data on the entropies required to reach possible phase transitions for different values of B x .…”
Section: Discussionmentioning
confidence: 99%